AN ARISTOTELIAN APPROACH TO ARISTOPHANES’ LYSISTRATA - Ayyıldız, Nilay Erdem (My University, 2018)
Comedy, which developed as a literary genre after tragedy, is a popular dramatic form in ancient Greek literature. In accordance with the periods of time through which it differs, comedy as a genre is divided into three types; Old Comedy, Middle Comedy and New Comedy. Regarded as a surviving manuscript of Old Comedy, Aristophanes’ Lysistrata provides evidence about the features of Old Comedy. Therefore, the aim of the study is to examine the play by focusing on the features which Aristotle seeks in a tragedy, which he regards as the best dramatic form. Through an Aristotelian reading of the play, the study reveals that although the play as comedy shares a lot of features with tragedy, it differs from tragedy in terms of content, language and characters.
Keywords: Tarih; Ortaçağ ve Rönesans Çalışmaları; Beşeri Bilimler; Edebiyat; Edebi Teori ve Eleştiri